“Estrategias de mercadeo de la imprenta dos hermanos en la ciudad de Babahoyo” - García Paredes, Yare Noemi (2022)
The frequency of changes that occur in today's society, makes businesses must meet new needs, so it is important to consider that not only should have a focus on external communication, but it is essential to prioritize the improvement of internal processes, to add more value to the service and consequently act strategically in the market, being possible to consolidate the brand, position it, and thus promote the volume of sales. The objective of this research is to analyze the marketing strategies of Imprenta Dos Hermanos in the city of Babahoyo, since the business registers a low level of sales, as a result of the fact that the commercial procedures are not effective, having as a determinant the absence of innovation in both internal and external issues, This does not allow reaching consumers and capturing their attention respectively, therefore, customers have a greater preference for the offers of the competition, which have developed techniques to create ongoing relationships with their users, taking into account the current situation, where they have improved their services to offer simplicity or other benefits to the buyer. To develop this study, the exploratory methodology was applied, together with the deductive method, with the purpose of reviewing qualitative and quantitative data on the case, so that it was possible to conclude that the actions focused on promotion, advertising and sales are executed in a wrong way, being necessary to consider the reality of the target audience, prior to establish strategies to present the offers and get the commercial interest of consumers.